Iceberg danger in the seas of the Russian Federation Arctic Zone under modern climate change conditions - I. A. Bychkova; V. G. Smirnov; S. V. Mikhaltseva; E. V. Platonova; И. А. Бычкова; В. Г. Смирнов; С. В. Михальцева; Е. В. Платонова (Environmental Evidence, 2024)
The aim of the research was to study the relationship between the intensity of iceberg formation in the Russian Arctic including the number of icebergs calving annually from outlet glaciers and surface air temperature anomalies. The research was carried out on the basis of satellite monitoring using non-commercial, freely distributed satellite information from optical-electronic satellites Landsat-8 (spatial resolution 15 m) and Sentinel-2 (spatial resolution 10 m) and the radar satellite Sentinel-1 (pixel size 20×40 m). To achieve the aim, an iceberg detection technique was used based on statistical criteria for searching for gradient zones in the analysis of two-dimensional fields of satellite images. Based on the analysis of satellite data of the visible spectral range of the Landsat-8 and Sentinel-2 satellites and Sentinel-1 radar data the maximum spatial dimensions of icebergs formed by the outlet glaciers of Severnaya Zemlya, Franz Josef Land (ZFI) and Novaya Zemlya in 2012–2022 were estimated. Satellite monitoring of the Severnaya Zemlya region was carried out using visible range images in the spring season (March–May), characterized by the best observation conditions in terms of cloudiness, natural light, and monitoring of icebergs most of which are located in fast ice at this time. Monitoring of the ZFI area was carried out using radar data in the period August-September, corresponding to the minimal ice cover conditions. Satellite monitoring of the Novaya Zemlya region was carried out using visible images in the summer season. In total, about 500 satellite images were analyzed. The discusses the dependence of the intensity of the iceberg formation process on the ice shelf and outlet glaciers with a floating edge on the surface air temperature and the maximum thickness of fast ice. It is shown that the abnormally warm weather that set in 2020 during the period of ice melting led to a sharp intensification of the process of glacier melting in the Russian Arctic and the formation of almost 8,000 icebergs ...